Study on the Weight and Patterns of Key Controlling Factors for Corrosion in Gathering and Transportation Pipelines of the Sulige Gas Field - JIANG Chengyin, LI Qiongwei, BAI Zilong, HAN Zizi, HUI Baoping, ZHANG Ruoyin, LIU Wei (Cailiao Baohu)
Since the western part of the Sulige Gas Field is a water-bearing gas reservoir， the pipelines are prone to corrosion， which severely affects the normal production operations of the gas field and results in significant economic losses and safety risks.In this study， the corrosion of gathering and transportation pipelines in the target gas field was analyzed.Based on this analysis， corrosion coupon experiments， scanning electron microscopy (SEM)， confocal Raman microscopy and X-ray diffraction (XRD) techniques were employed， combined with water and gas quality analyses， to investigate the corrosion patterns of the pipelines.The primary controlling factors of corrosion， including chloride ions，microorganisms， CO2 partial pressure， total pressure and flow rate， were identified.Furthermore， the weight of each controlling factor was determined according to different corrosion characteristics.Results showed that when uniform corrosion of the samples was used as the evaluation criterion， the CO2 partial pressure had the greatest influence on the corrosion rate， accounting for 58.00%of the weight.When pitting corrosion of the samples was used as the evaluation criterion， microorganisms had the greatest influence on the corrosion rate， accounting for 34.00%of the weight.